Book review on Ayurvedic Treatments of Kerala - Aswathy V J; Subin, V R; Jigeesh, P P (International Research Journal of Ayurveda & Yoga, 2024)
Kerala physicians have made significant contributions to Ayurvedic literature by documenting their clinical experiences. Many of these texts emphasize Panchakarma and its preparatory stages, crucial components of Ayurvedic treatment. This publication aims to promote the practice of Panchakarma in Kerala, offering detailed explanations of unique Kerala therapies like Pizhichil, Navara kizhi, Sirovasti, Siraseka, along with dietary recommendations. The book also addresses challenges encountered during Keraleeya kriya kramas. Delving into various Keraleeya kriya krama procedures such as Pindasweda, Annalepanam, Kayasekam/Pizhichil, Sirovasthi, Sirosekam/Dhara, and Sirolepanam, it draws from personal experiences to elucidate concepts like diet and daily routines during and after treatment. Additionally, the book discusses the instruments used and provides relevant formulations. Despite primarily focusing on six prevalent procedures, it also covers essential aspects like diet plans and sleep schedules, presenting the author’s creative insights in a scientifically sound manner through detailed descriptions of techniques.